Introduction : Professional development in CALL: a selection of papers - Papadima-Sophocleous, Salomi; Giannikas, Christina N.; Kakoulli-Constantinou, Elis (My University, 2019)
Language teaching instruction has evolved substantially over the past two decades. The changes lie within the evident increase of using new technologies in formal educational settings. Universities, schools, and language institutions across the globe are encouraging educators to use technology tools which will assist in teaching foreign languages effectively. Nonetheless, sufficient Computer Assisted Language Learning (CALL) training is lacking in teacher preparation programmes, even though there is a growing universal interest in technology-proficient language teachers among institutions...
Keywords: Teacher education; CALL; Content knowledge; Professional development; Educational technology; Teacher training